ISOLASI, KARAKTERISASI DAN IDENTIFIKASI BAKTERI ENDOFIT KULIT BATANG SRIKAYA (ANNONA SQUAMOSA) DAN POTENSINYA SEBAGAI ANTIBAKTERI - Lalu Zulkifli; Dwi Soelistya Dyah Jekti; Samsul Bahri (Jurnal Penelitian Pendidikan IPA, 2018)
The objective of this study was to isolate endophytic bacteria from bark of srikaya, analyzing antibacterial activity of endophytic bacteria in S. aureus, B. cereus and E. coli pathogenic bacteria, characterizing endophytic bacteria capable of inhibiting the growth of pathogenic bacteria and identification of endophytic bacteria able to inhibit the growth of pathogenic bacteria. Isolation of endophytic bacteria using TSA and NA media, bioassay on pathogen bacteria with concentration of 106 cells / ml with using Ø 6 mm wells and entering supernatant of 100 μl. Supernatant was obtained by growing endophytic bacteria in NB media shaken with shaker 150 cycles / min for 48 h at 32ᵒC then culture centrifuge at 5000 g for 30 min. Positive control using cyprofloxacin. Characterization is based on the nature of the colony, Gram paint, spore formation, and biochemical tests. The results of the study yielded 13 endophytic bacterial isolates and 4 endophytic isolates capable of inhibiting the growth of 8 pathogenic bacteria with sensitive criteria, 2 pathogenic bacteria with resistant criteria and 1 pathogen bacteria can not be inhibited its growth. Gram's paint results show that 4 endophytic isolates belong to Gram-positive, rod-shaped and spore forming cells. From the character possessed by the bacteria can be identified that the 4 bacteria endofit capable of inhibiting pathogenic bacteria are Bacillus brevis, Bacillus latesporus, Virgibacillus pantothenticus, and Bacillus circulansKeywords: Characterization, Endophytic Bacteria, Bark of Srikaya, Antibacterial